The Politicization of Media Discourse in the Murder of the Journalist Jamal Khashoggi: The News Websites of Aljazeera and the Washington Post as Models - Hasan Mohammad AlMomani; Lana Khalid Atiyyat (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study seeks to identify the features of media politicization in the murder of the journalist Jamal Khashoggi in the content of the News Websites of Al Jazeera and Washington Post. Moreover, this study will also identify the consistency of the content and characteristics of the media discourse. This study has employed discourse analysis approach so to analyze (20) articles that have been picked out randomly as a study sample published by news websites of Al-Jazeera Washington Post. This study has revealed that Al-Jazeera and Washington Post have changed their style that used to convey news from neutrality to accusing Saudi Arabia of assasinating Khashoggi. Regarding the media discourse, the study concludes that, articles from both Al-Jazeera's and Washington Post have contained all elements of influential media discourse, including consistency, harmony, comparative, and rhetorical images. This study recommends that there should be international charters and laws to govern politicized media and regulate news coverage constructively and objectively.